A Methodology for Monitoring Rail Punctuality Improvements - C. W. Palmqvist; I. Kristoffersson (IEEE Open Journal of Intelligent Transportation Systems, 2022)
Punctuality is an important aspect of train operations, highly valued by passengers. Both Swedish and Norwegian railways have introduced frameworks to systematically improve punctuality in their systems, inspired by an extensive literature on Total Quality Management. After about a decade with these frameworks, we can see that punctuality has risen by about 2–3 percentage points. However, this pace of improvements is slower than desired. We propose that there is a gap between what most individual improvement efforts deliver, and what can be detected by directly monitoring punctuality. This gap stifles the desired culture of constant improvements. We instead propose a methodology for how to monitor punctuality improvements, by focusing on the constituents of a train trip. Using 20 years of data from commuter trains in three metropolitan regions (Stockholm, Gothenburg & Malmö), we show the frequency of runtime and dwell time delays is directly related to punctuality. These delay frequencies are also easy to measure and target, and more easily capture the intended effects of specific improvement efforts. Our hope is that this framework and measures such as these will better enable systematic efforts to improve railway punctuality.